2023
DOI: 10.1038/s41562-023-01637-2
|View full text |Cite
|
Sign up to set email alerts
|

The future of academic publishing

Abstract: Harnessing the utility of preprints may solve many of these issues in academic publishing. Preprints are defined broadly as research documents made freely available via a public server (e.g., arXiv; PsyArXiv) before publication in a journal. They accelerate dissemination of research, allow researchers to gain early feedback, and increase access. With many concerns surrounding their use unfounded (e.g., scooping 10,11 ), preprints can reduce publication bias by permitting researchers to deposit their work regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…There is an important role of selective publishing in the misinterpretation of a meta-analysis 75 , highlighting the need for new practices regarding the publication of non-significant results. Even if this represents a complex, deep-rooted issue that requires a change in the whole culture of publishing scientific data, some authors have been raising this discussion and proposing alternatives 76 79 . However, the results of our publication bias analysis should be interpreted with caution, as our funnel plots were based on SMD versus standard error (SE).…”
Section: Discussionmentioning
confidence: 99%
“…There is an important role of selective publishing in the misinterpretation of a meta-analysis 75 , highlighting the need for new practices regarding the publication of non-significant results. Even if this represents a complex, deep-rooted issue that requires a change in the whole culture of publishing scientific data, some authors have been raising this discussion and proposing alternatives 76 79 . However, the results of our publication bias analysis should be interpreted with caution, as our funnel plots were based on SMD versus standard error (SE).…”
Section: Discussionmentioning
confidence: 99%
“…More articles should be open access, given that practitioners have long cited access as a barrier to engaging with journals (Tucker and Lowe, 2014). Social marketing (and marketing as a whole) journals could take the lead of the Latin America science community where 95% are open access thanks to non-commercial public funding (Ahmed et al , 2023). The authors have engaged in much dialogue whilst writing this paper about the need for all articles to be open access (i.e.…”
Section: Recommendationsmentioning
confidence: 99%
“…Journal editors are finding it increasingly challenging to find appropriate reviewers 2 . There might be several reasons for this, with lack of time being the most commonly cited reason.…”
Section: Challenges With Peer Reviewmentioning
confidence: 99%
“…Similarly, publication procedures and policies also need to rapidly evolve in order to keep up with advancements in modern technology, and also to overcome the challenges with the traditional peer‐review process. Some have suggested that peer review is no longer needed and many researchers are availing of the opportunity to pre‐print without peer review 2 . A recent paper comparing the quality of pre‐print and peer‐review articles concluded that the quality of reporting in pre‐prints in the life sciences was relatively similar to that of peer‐reviewed articles, supporting the idea that preprints should be considered valid scientific contributions 3 .…”
Section: Do We Still Need Peer Reviewing?mentioning
confidence: 99%